Importance of HPV Genotyping for the Screening, Therapy and Management of Cervical Neoplasias - Jentschke, M.; Soergel, P.; Hillemanns, P. (Geburtshilfe und Frauenheilkunde, 2012)
In the last decade, the detection of human papillomaviruses (HPV) has become increasingly important in cervical cancer screening and the treatment of cancer precursors. HPV screening is recommended for the further evaluation of abnormal Pap tests or during follow-up after treating precancerous lesions. Several randomised controlled studies have shown that screening for cervical cancer using HPV detection can be more effective than cytology alone. Genotyping of different high-risk HPV (hrHPV) types obtained from smear tests has not yet gained widespread acceptance in clinical practice. However, significant differences have been noted in the oncogenicity of hrHPV genotypes. HPV 16 is by far the most common and oncogenic genotype. Genotyping of hrHPV could be helpful for the risk stratification of HPV-positive women.
Keywords: cervical cancer; cervical interepithelial neoplasia (CIN); human papillomavirus